Implementasi Model Pembelajaran GGE sebagai Upaya Peningkatan Keterampilan Softskill Mahasiswa Pendidikan Ekonomi - Cahyo Apri Setiaji; Cahyo Setiaji; Anita Rinawati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to improve the soft skills of students' aspects of cooperation and social communication by implementing the GGE learning model. The problem is focused on efforts to improve cooperation and social communication skills. Pre-cycle identification of obtaining results related to the aspect of cooperation still needs to be improved because it is at the level of moderate, sufficient and insufficient interpretation of each indicator. The main indicators of the social communication aspect are at the level of adequate interpretation. The research data were collected using a checklist and observation sheets by observing the changes that occurred in students during two cycles. This study concludes that the GGE model can improve soft skills in the aspects of cooperation and social communication. Aspects of cooperation, indicators of respect for opinions and light-heartedness increased from moderate and moderate levels in pre-cycle to high levels in cycle 2, responsibility at moderate level in pre-cycle increased to very high level in cycle 2, participatory increased from moderate level to very high level in cycle 2 Aspects of social communication also experienced an increase in indicators of confidence, language style, speech style, and body gestures from a moderate level in the pre-cycle to a high level in cycle 2. The indicators of concept mastery and calmness were at a moderate level in the pre-cycle, increasing to a very high level in the pre-cycle. cycle 2.